Cognitive Impairment in Renal Replacement Therapy: Comparison between Methods - Giuseppe, Paribello; Fortuna, Papa; Chiara, Ganzerli Maria; Chiara, Del Prete; Caterina, Lanzuise; Ivana, Capuano; Daniela, Pacella; Giuseppina, Sannino; Gianluca, Rompianesi; Antonio, Pisani; Eleonora, Riccio (Journal of Clinical Nephrology, 2024)
Cognitive impairment (CI) can be defined as a clinical syndrome characterized by a decline in at least two of several domains of cognitive function. Chronic kidney disease (CKD) is an independent risk factor for cognitive decline, and the prevalence in patients with end-stage renal disease is estimated at 50% - 80%. However, it appears that CI in patients on renal replacement therapy (RRT) may be underdiagnosed. In this cross-sectional study, 33 patients on Peritoneal Dialysis from the AOU Federico II were recruited, and matched by sex, age, and dialysis age to 33 patients on Hemodialysis and 33 controls belonging to healthy volunteers. The total 66 patients and their 33 controls were assessed for cognitive function using the Cognitive Reserve Index Questionnaire (CRIq) test. Between PD and HD patients, a statistically significant difference emerged in all subscores and in the total CRI. Between PD patients and controls, a statistically significant difference emerged in education, CRI- CRI-leisure time, and the total CRI. Therefore, CI may occur in patients undergoing PD earlier and with a greater frequency than in the general population, but with a lower incidence than in patients on HD. These considerations should be communicated to patients when they are educated about different replacement methods.